EFEKTIVITAS TERAPI AKUPUNKTUR TERHADAP PERUBAHAN SKALA NYERI VAS PADA LANSIA PASCA MENOPAUSE DENGAN NYERI MUSKULOSKELETAL - Listina Ade Widya Ningtyas; Ni Made Dwi Purnamayanti; I Made Sukarja (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2026)
Postmenopausal older women commonly experience musculoskeletal pain, which may interfere with daily activities, reduce productivity, and limit their ability to perform physical activities independently. This study aimed to evaluate the effectiveness of acupuncture therapy in reducing pain intensity among postmenopausal older women with musculoskeletal pain. An analytical experimental study was conducted at the UPTD Community Health Center I, West Denpasar Health Office, Bali, Indonesia, from May to September 2025. A total of 30 participants were recruited using purposive sampling and equally allocated into two groups. The intervention group received three sessions of acupuncture therapy, while the control group participated in exercise therapy. Pain intensity was assessed using the Visual Analog Scale (VAS). Data were analyzed using the Mann–Whitney U test to compare pain scores between the two groups following the intervention. The results showed a statistically significant difference in pain intensity between the acupuncture and control groups (Asymp. Sig. [2-tailed] < 0,001). The superior pain reduction observed in the acupuncture group may be attributed to its analgesic mechanism through the gate control theory of pain. Acupuncture is believed to stimulate A-beta nerve fibers in the skin and muscles, promoting the release of endogenous opioids, including endorphins, enkephalins, and dynorphins, which contribute to pain relief. These findings suggest that acupuncture is an effective non-pharmacological intervention for reducing musculoskeletal pain in postmenopausal older women.